Correlates and prognostic impact of acute heart failure at the acute stage of ST-elevation and non-ST-elevation myocardial infarction according to diabetic status: the FAST-MI registries. (25th November 2020) - Dillinger, J.G; Achkouty, G; Albert, F; Labeque, J.N; Morelle, J.F; Cottin, Y; Lim, P; Schiele, F; Ferrieres, J; Henry, P; Puymirat, E; Simon, T; et al.
Abstract: Background: Diabetes mellitus (DM) predisposes to cardiovascular diseases including acute myocardial infarction (AMI) and acute heart failure (AHF). Purpose: Analysing the French Registries of Acute ST-elevation and non-ST-elevation Myocardial Infarction (FAST-MI) 2005 and 2010, we assessed correlates of AHF occurring at the acute stage of ST-elevation AMI (STEMI) and non-ST-elevation AMI (NSTEMI), as well as the prognostic impact of AHF on 5-year mortality according to diabetic status. Methods: The FAST-MI 2005 and 2010 registries included 7, 839 consecutive patients admitted for AMI (4, 250 STEMI and 3, 589 NSTEMI). Vital status at 5 years was available in >96% of the patients. Binary logistic regression analysis was used to determine independent correlates of AHF and Cox multivariate analysis was used to determine independent correlates of 5-year mortality. Long-term survival curves were estimated using the Kaplan Meier method and comparisons were made using log-rank tests. Results: 2, 151 patients presented with DM (27, 4%) and 629 patients (8, 0%) were treated by insulin (DMi). DM patients were older (70.0 vs. 64.6 years; p<0.001), with more comorbidities and more severe coronary artery disease. AHF (pulmonary edema or cardiogenic shock) was the most frequent in-hospital complication (12.5%) and was twice as frequent in DM patients (20.2% vs. 9.6%; adjusted OR=1.66; 95% confidence interval: 1.43–1.94; P<0.001). AHF was more frequently observed in DM patients on insulin therapy compared with DM patients not receiving insulin (29.1% vs 16.6%; adjusted OR=1.53; 95% CI: 1.20–1.96; P=0.001). The significant difference in AHF between DM patients and patients without DM was found in both STEMI (18.8% vs 8.0%; P=0.001) and in NSTEMI (21.3% vs 11.9%; P=0.001) patients. After multivariate analysis on confounders (risk factors, previous medical history, type of AMI, year of survey and medications used before the index AMI), compared with patients without DM nor AHF, those with AHF without DM and those with DM without AHF had a 50% increase in 5-year mortality (adjusted HR=1.50; 95% CI: 1.32–1.69; P<0.001 and adjusted HR=1.46; 95% CI: 1.23–1.74; P<0.001) while the risk of 5-year death was doubled in those with both DM and AHF (adjusted HR=1.97; 95% CI: 1.66–2.34; P<0.0001). Conclusion: AHF is the most frequent complication of AMI and is twice as common in DM patients. It is associated with reduced 5-year survival in non-diabetic and DM patients, with the worst outcomes in patients with both conditions (AHF and DM). In AMI, new management strategies are needed to prevent AHF and improve survival in DM patients with AHF. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The FAST-MI 2005 and 2010 registries are the propriety of the French Society of Cardiology and were funded by grants from the following companies: Amgen, AstraZeneca, Bayer, BMS, Daiichi-Sankyo, Eli-Lilly, GSK, MSD, Novartis, Pfizer, Sanofi, and Servier, and by a grant from the French National Health Insurance body (CNAM-TS).